1997
DOI: 10.1023/a:1026204527786
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ability of managed care organizations to provide ongoing prenatal care to Medicaid populations in a cost-effective manner depends partly on their development of packages of prenatal services that foster positive preventive health care utilization behaviors and good pregnancy outcomes. The results of this project suggest that the intervention was beneficial in the area of improving utilization of prenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Positive associations between comprehensive care coordination and improved pregnancy outcomes have been observed in studies from such geographically diverse locations as Minnesota, California, Florida, and North Carolina, to name but a few. While these studies employed different income levels, the generally comparable direction of the results adds to the collective interpretation that these services are beneficial (Buescher, et al, 1991;Alexander et al, 1997;Simpson et al, 1997;Long and Marques, 1998).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Positive associations between comprehensive care coordination and improved pregnancy outcomes have been observed in studies from such geographically diverse locations as Minnesota, California, Florida, and North Carolina, to name but a few. While these studies employed different income levels, the generally comparable direction of the results adds to the collective interpretation that these services are beneficial (Buescher, et al, 1991;Alexander et al, 1997;Simpson et al, 1997;Long and Marques, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, the authors chose term-SGA as the indicator of pregnancy outcome because previous literature has suggested that prenatal care through nutritional services and counseling is associated with reductions in term-SGA (Alexander et al, 1997). Further, SGA has preventive health significance because of an association with problems of lower cognitive performance, lessened educational achievement, impaired growth and development, and diminished motor ability (Paz et al, 1996;Pryor et al, 1995;Goldenberg et al, 1996;Karlberg et al, 1996;Hutton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the authors chose term-SGA as the indicator of pregnancy outcome because previous literature has suggested that prenatal care through nutritional services and counseling is associated with reductions in term-SGA (Alexander et al, 1997). Further, SGA has preventive health significance because of an association with problems of lower cognitive performance, lessened educational achievement, impaired growth and development, and diminished motor ability (Paz et al, 1996;Pryor et al, 1995;Goldenberg et al, 1996;Karlberg et al, 1996;Hutton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%